Erythromycin induction of clindamycin resistance in Staphylococcus aureus isolated from three hospitals in Lima, Peru - Tamariz Ortiz, Jesús Humberto (2009)
Background: Staphylococcus aureus is an important pathogen envolved in many infections, and it has a greater impact because of its many virulence factors and antimicrobial resistance. Erythromycin-induced clindamycin resistance in S. aureus is an increasing problem in different parts of the world.Objectives: To determine the frequency of Erythromycin-induced clindamycin resistance in S. aureus isolates from three hospitals in Lima, Peru. To determine the presence of MRSA-MLSBi among these strains and their relationship with the biological origin of the resistant strains.Material and methods: 272 Staphyloccus aureus strains were isolated in Cayetano Heredia National Hospital, The National Institute for Cancer, and The Children National Health Institute between May 2005 and September 2006. Resistance to methycillin resistance was determined using the Oxacillin Agar Screen, and erythromycin-induced clindamycin resistance was assessed using the dual-disc agar diffusion methods (D-test). MLSBi phenotypes were also identified.Results: We found 13 D-test positive S. aureus strains, 9 (3.3%) of them were MSSA and 4 were MRSA (1.5%). Total resistance to clindamicyn (constitutive and inductive) was found in 48.2% of the total Straits tested.Conclusion: The frequency of Erythromycin-induced clindamycin resistance in S. aureus strains in our country is still low in both methycillin-susceptible and methycillin-resistant strains.